Diabetes and diabetes care among non-obese South Asian Americans: Findings from a population-based study. Issue 1 (January 2019) - Chan, Keith; De Souza, Leanne R.; Kobayashi, Karen; Fuller-Thomson, Esme
Abstract: Aims: The aim of this paper is to provide population-based data from California on: (a) the prevalence and the odds of diabetes among non-obese South Asian (SA) Americans compared to non-Hispanic Whites (NHW); (b) to assess the prevalence and odds of optimal medical care including regular eye exams, foot exams, and the monitoring of hemoglobin A1C blood glucose levels; and (c) To identify the factors that are associated with diabetes among SA Americans. Methods: The combined 2007, 2009, and 2011 waves of the adult California Health Interview Survey (CHIS) was used to analyze a non-obese (BMI<30) sample of 1251 SA and 72, 072 NHW. Chi-square and logistic regression analyses were performed using Stata. Results: Non-obese SA had more than twice the odds of diabetes in comparison to NHW (OR = 2.50; 1.66, 3.76), even after adjusting for sociodemographic characteristics. Despite their higher propensity for diabetes, there were no significant ethnic differences in the level of optimal care received by those with diabetes. Among non-obese South Asian Americans, the odds of diabetes were higher for older respondents, those without a post-secondary degree, those who were foreign-born, those who had ever smoked, and those with BMI from 25 to 29.99. Conclusions: Non-obese SA in California experience a disproportionately higher prevalence of diabetes than their NHW counterparts.